(untitled) (Research, Society and Development, 2025)
The teaching of Human Anatomy is fundamental for the training of undergraduate health courses. However, the complexity of the content, combined with ethical, religious, cultural, and bureaucratic issues related to the use of cadavers as a traditional teaching resource, poses challenges to the teaching-learning process. Furthermore, the difficulty of accessing this teaching resource and the need for pedagogical updates highlight the importance of adopting new methodologies. Thus, this study aimed to analyze innovative practices applied to the teaching of Anatomy through an integrative literature review conducted covering the period between September 2022 and July 2025. Articles were selected from the SciELO (7), Virtual Health Library – BVS (4), and CAPES Journals Portal (7) databases, totaling 18 studies. The results were organized into five thematic categories: active methodologies, artistic approaches, digital technologies, dissection activities, and extension activities. It is concluded that the use of diversified methodologies allows for better adaptation to institutional and student realities, in addition to promoting meaningful learning, contributing to the more comprehensive training of health professionals.